Missed pathological femoral neck fracture undergoes spontaneous healing - Adrian C. Kong, MS (Elsevier, 2022)
Pathologic fractures are common complications of metastatic bone disease in patients with breast cancer. Fractures involving the proximal femur generally cause significant pain that is exacerbated by ambulation. Due to excessive stress on the weight-bearing hip joint, these fractures present a significant burden on the quality of life among patients. Here we describe a case of a 38-year-old female patient who was found to have a pathologic fracture of the proximal femur missed on imaging studies that underwent spontaneous union. Pathologic fractures rarely heal on their own, since a tumor at the fracture site interferes with bone healing and most fractures have to be managed with surgical intervention. Fractures can be missed on imaging studies in the setting of extensive metastatic disease. Physicians should be cognizant of this fact and maintain a high level of suspicion to recognize fractures with unusual presentations where patients may not present with the typical findings of acute onset of pain and inability to ambulate or bear weight.